Integrasi Kurikulum Pesantren dan Kurikulum Nasional di Madrasah Mu’allimin Mu’alimat 6 Tahun Tambakberas Jombang - Khasanatun Na’imah; Wahyudi Wahyudi (YASIN, 2026)
Although the integration of the pesantren curriculum and the national curriculum has received attention in several previous studies, research that specifically discusses its systematic implementation at the planning, implementation, and evaluation stages in the context of a six-year madrasah remains limited. This study aims to describe the concept of integrating the pesantren curriculum and the national curriculum and to analyze the supporting and inhibiting factors in its implementation. This study used a qualitative approach with a case study design, involving the Vice Principal for Curriculum as the main informant selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using the Miles and Huberman model of thematic analysis through the stages of data reduction, data display, and conclusion drawing. The results showed that curriculum integration was implemented through three systematic stages, namely planning in the form of curriculum integration and strengthening of pesantren subjects, implementation through integrated daily scheduling without rigid separation, and evaluation through periodic assessment by the curriculum development team. Supporting factors for the integration included adequate facilities, the use of academic technology, and qualified teacher backgrounds, whereas inhibiting factors included suboptimal student discipline and some teachers who were not yet optimal in delivering the material. These findings contribute to the development of an integrative curriculum model in Islamic education and broaden understanding of pesantren-based formal education management. Thus, systematic curriculum integration is important for balancing academic achievement and spiritual formation, while also providing practical implications for madrasah leaders, teachers, and policymakers in strengthening teacher training, discipline systems, and effective dual-curriculum management.